Developing and Validating a New Scale to Assess Signs of Neglect of Infants and Caregivers - Arimoto, Azusa (Journal of interpersonal violence, 2021)
This study aimed to develop a scale assessing the early signs of infant neglect and to test its reliability and validity. Neglect is a frequent type of child maltreatment and a serious problem worldwide, but it has received limited research attention. Previous studies of neglect assessment have mainly been targeted toward assessing the risk of apparent neglectful caregivers and neglected children. Early needs assessment scale focused on neglect evaluated by public health professionals in infants is necessary for the urgency of preventing neglect from infancy. Participants were community/public health nurses across Japan with experience working with neglectful caregivers of infants. The initial Signs of Neglect in Infants Assessment Scale (SIGN) was developed and refined based on previous studies, community/public health nurse consultation, and expert review. In 2017, 474 community/public health nurses completed a questionnaire regarding one infant neglect case. Item analysis, exploratory factor analysis, confirmatory factor analysis, and comparisons with a preexisting scale and case reporting status were used to narrow the scale and assess its psychometric properties. Item and exploratory factor analyses reduced the scale to 14 items on three factors: lack of basic supervisory care, child underdevelopment, and lack of emotional behavior. A confirmatory factor analysis indicated a good model fit (adjusted goodness-of-fit index = 0.921). Cronbach’s alpha was >.80 for total SIGN and all three factors. SIGN score was positively correlated with the preexisting scale (r = .335, p < .001) and with child protection services reporting status (M = 12.8 for reported cases vs. 9.2 for unreported cases, p < .001). The SIGN is an innovative scale with good psychometric properties for assessing signs of infant neglect. It has the potential to contribute to preventing infant neglect by providing early support to infants and their caregivers.